Application of Various Mechanical Treatments for Meat Tenderization - Mohamad Afifi Ismail; Gun Hean Chong; Mohammad Rashedi Ismail-Fitry (Journal of Advanced Research Design, 2023)
Meat tenderness is an important quality attribute that influences consumer acceptance. The application of mechanical treatment by mean to reduce toughness of meat cuts has gained much interest recently with an intention to make use of the lower grade meat cuts. This review deliberates the function, mechanism and numerous types of mechanical work in meat tenderization. The mechanical work employs to make meat softer by loosening the muscle structure and disrupting muscle cell. Previous studies have thoroughly examined the use of mechanical treatment (such as massaging, tumbling, and grinding) as an effective meat tenderization technique. Besides that, current research on newly emerging processing technology such as high-pressure process (HPP) also shows potential to be explored. The application of mechanical work has shown impressive outcomes by reducing the shear force value that represents the hardness of meat. The present paper also described the physical, biochemical and the structural changes of the meat. Finally, the improvements in the meat tenderness by using various type of mechanical work are presented in this paper.